Nietzsche on memory and history the re-encountered shadow - Jensen, Anthony K., 1978-; Santini, Carlotta, 1984- (Walter de Gruyter, 2021)
History and memory rank as central themes in the philosophy of Friedrich Nietzsche. As one of the last philosophers of the 19th century, Nietzsche naturally belongs to the so-called "historical century". The contentious exchange with the past and with antiquity -- as much as the mechanisms, the dangers, and the lessons of memory and tradition -- are continually examined and stand in close relationship with Nietzsche's vision of life and his project of human development. As Jacob Burckhardt once wrote of the cultural critique to his Basel colleague: "Fundamentally, you are always teaching history" (9/13/1882). Following Burckhardt's judgment, the contributors focus on the analysis of core questions in the philosophies of history and memory, and their respective convergence in the thought of Nietzsche. The epistemological relevance of these central concepts will be thematized alongside those concerning tradition, and education. The discussion of these rich themes unifies a broad spectrum of questions, ranging from cultural memory to contemporary philosophy of mind. The contributions are revised versions of selected papers presented at the 2018 conference of the annual meeting of the Nietzsche Society in Naumburg.